Formulation, optimization, and standardization of orodispersible herbal tablets using design of experiments (DOE) - Shinde, Ganesh; Jadhav, Ravindra; Godge, Rahul; Vikhe, Dattaprasad; Tambe, Vishal; Khule, Shubham (Creative Pharma Assent, 2025)
Background: This study aimed to develop and optimize an orodispersible herbal tablet incorporating Achyranthes aspera Linn extract. Sodium Starch Glycolate and Crospovidone were employed as superdisintegrants to promote rapid tablet disintegration, while β-cyclodextrin was utilized to enhance the solubility of specific constituents within the extract. The optimized formulation exhibited a rapid disintegration time of 1.805 seconds and achieved a cumulative drug release of 98.04%, indicating improved dissolution and potential enhancement in oral bioavailability. Methodology: Orodispersible tablets were formulated using Design of Experiments (DOE) software, with crospovidone and sodium starch glycolate as independent variables, and time of disintegration and cumulative drug release as dependent variables. The formulation was evaluated for weight variation, uniformity, hardness, wetting time, and in vitro dispersion time. Result & Discussion: The optimized F6 batch of orodispersible herbal tablets demonstrated the following characteristics: hardness of 2.98 kg/cm², friability of 0.58%, weight variation of 3.319%, disintegration time of 13.805 seconds, wetting time of 34.4 seconds, content uniformity of 99.5%, water absorption of 36%, and cumulative drug release of 98.04%, all within the permissible limits as per official pharmacopoeialstandards. Conclusion: The study concludes that crospovidone and sodium starch glycolate effectively reduce disintegration time and improve cumulative drug release. These findings validate the reliability of the model, with minor deviations attributed to experimental variability.